2003
DOI: 10.1046/j.1365-2672.2003.02033.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of human isolates of Salmonella enterica serovar Enteritidis in Malaysia

Abstract: Aims:The study was undertaken to determine clonal relationship and genetic diversity of the human strains of Salmonella enterica serovar Enteritidis isolated from 1995 to 2002 from different parts of Malaysia. Methods and Results: Antimicrobial susceptibility test, plasmid profiling and pulsed-field gel electrophoresis were applied to analyse 65 human isolates of S. Enteritidis obtained over an eight year period from different parts of Malaysia. Four nonhuman isolates were included for comparison. A total of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 29 publications
2
18
0
Order By: Relevance
“…Enteritidis plasmid of size 55 kb is commonly found among the majority of Salm. Enteritidis isolates and has been denoted the serovar‐specific plasmid (Bakeri et al. 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Enteritidis plasmid of size 55 kb is commonly found among the majority of Salm. Enteritidis isolates and has been denoted the serovar‐specific plasmid (Bakeri et al. 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Salmonellosis is caused by two species of Salmonella (Salmonella enterica and Salmonella bongori), which are etiological agents for diarrhoeal and systemic infection in humans. Human infections with non-typhoidal Salmonella (NTS) are frequently associated with the consumption of contaminated food [1]. This can result in diarrhoeal disease, bacteraemia and extraintestinal focal infection in infants such as meningitis, and may also result in more serious complications among the elderly and immunocompromised patients [2].…”
Section: Introductionmentioning
confidence: 99%
“…Such mutation may remove or create recognition sites through insertion, deletion, translocation and inversion, or by mobile genetic elements. The assumption is that as time passes and organisms spread, divergence may occur [4]. This study also showed that both PFGE and phage typing were capable of differentiating S. Enteritidis strains.…”
Section: Discussionmentioning
confidence: 55%